Metal organic framework magnetic material, preparation method, device for removing PS micro-plastic in water and application

By preparing Zn/MIL-101(Fe)@Fe3O4 magnetic material, the problem of metal organic frame materials being difficult to recycle and poor adsorption capacity when adsorbing PS microplastics is solved, and efficient material recycling and strong adsorption effect is achieved.

CN119680522APending Publication Date: 2025-03-25INNER MONGOLIA AGRICULTURAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510078020.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In the prior art, when using metal organic frame materials to adsorb PS microplastics, the material is not easy to recycle and has poor adsorption capacity.

Method used

By preparing a metal organic frame magnetic material Zn/MIL-101(Fe)@Fe3O4, the magnetic properties of Fe3O4 particles are used to make the material easy to recover, and the adsorption capacity of the material is enhanced by the modification of Zn.

Benefits of technology

It realizes efficient material recycling and strong adsorption of PS microplastics, improving the recycling rate and practical application value of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680522A_ABST
    Figure CN119680522A_ABST
Patent Text Reader

Abstract

The invention relates to a metal organic framework magnetic material, a preparation method thereof, a device for removing PS (polystyrene) microplastics in water and application of the device, MIL-101 (Fe) and Fe3O4 particles are compounded through a one-step solvothermal method, and the loaded Fe3O4 component enables the metal organic framework material to have the capability of being separated and recycled through an external magnetic field. Zn is further used for secondary modification, the formed bimetallic coordination center greatly improves the electrostatic adsorption capacity of the synthetic material to PS micro-plastics, the original pore structure of the material is improved by adding Zn, more adsorption sites can be provided, and the adsorption capacity to the PS micro-plastics is increased. The functional composite material synthesized by the method shows more excellent adsorption capacity and removal effect when being applied to adsorption removal of PS in water, and is simple to operate, wide in pH application range and high in ion interference resistance. According to the device provided by the invention, the synthesized metal organic framework magnetic material is loaded, so that the continuous efficient removal of the PS micro-plastic in the water body and the efficient recovery of the material can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adsorbents for wastewater treatment and preparation methods thereof, and in particular to a metal organic framework magnetic material and a preparation method thereof, and a device for removing PS microplastics in water and applications thereof. Background Art

[0002] As a widely used high-molecular-weight organic polymer material, the problem of improper disposal of plastics has become increasingly prominent, resulting in a large amount of plastic waste entering the environment. Among them, microplastics, a specific form of plastic particles, have been widely distributed in nature as plastic derivatives. Researchers have found traces of them in rivers, lakes, reservoirs and oceans, and microplastic pollution has become a recognized global environmental problem. What is more worrying is that microplastics have been found to exist in organisms, which means that many organisms, including humans, are at risk of microplastic pollution. In addition, microplastics are susceptible to multiple complex effects such as ultraviolet oxidation, water erosion and biodegradation in the natural environment, resulting in changes in their surface structures such as texture and functional groups, further reduction in size, more active environmental behavior, and easier adsorption with other pollutants. In summary, microplastics have the characteristics of small size, difficulty in degradation, biotoxicity and bioaccumulation, and can be used as carriers of pollutants such as toxic metals and pesticides and coexist with pollutants, posing a potential threat to the ecological environment and human health. In view of the unique physical and chemical properties of microplastics, the development of efficient, low-cost and environmentally friendly microplastic treatment technology has become a technical problem that needs to be solved in the field of environmental protection.

[0003] Currently, although there are methods such as filtration, flotation, advanced oxidation and photocatalysis for the treatment of microplastics, these methods all have limitations. Specifically, the filtration method is difficult to effectively remove microplastics with fine particles; the removal efficiency of the flotation method is easily affected by the water quality; the advanced oxidation method may cause secondary environmental pollution; the degradation process of the photocatalytic method takes a long time and the catalyst is difficult to regenerate. In view of the shortcomings of the above methods, the adsorption method has become one of the widely used microplastic removal methods with its advantages of low cost, high efficiency, simple operation and high reuse rate.

[0004] The adsorption method usually uses porous materials as adsorption materials (i.e., adsorbents) for pollutants such as microplastics. Porous materials have the characteristics of high specific surface area and adjustable pore structure size, and show great potential in the fields of water pollutant treatment and energy storage. Among them, metal organic frameworks (MOFs), as a new type of polymer material, have the advantages of diverse types, rich structures, ultra-high specific surface area and porosity, adjustable pore size, and easy surface modification and functionalization compared to traditional porous materials. They have been widely used in the field of adsorption and separation. In order to optimize the treatment ability of metal organic frameworks (MOFs) for pollutants, their physical and chemical properties are often improved through technical means such as functional group modification, metal ion doping, or composite with other functional materials to adapt to complex treatment environments. Among them, MIL-101 (Fe), as one of the many metal organic frameworks (MOFs), has the characteristics of rigid structure, high porosity, strong chemical stability, and good hydrothermal stability, which makes it show good application prospects in water remediation.

[0005] Although metal organic frameworks (MOFs) have been widely used in the separation of pollutants such as heavy metals, antibiotics and dyes, there are few studies on the adsorption of microplastics such as polystyrene (PS). In addition, when using metal organic frameworks (MOFs) to adsorb water pollutants such as microplastics, their separation performance is poor, and they are not easy to be recovered and recycled. In addition, metal organic frameworks (MOFs) usually use single metal coordination centers, the material has fewer adsorption sites, and the adsorption capacity for microplastics such as PS is poor. Summary of the invention

[0006] The purpose of the present invention is to provide a metal organic framework magnetic material and a preparation method, a device and application for removing PS microplastics in water, so as to solve the technical problems that the metal organic framework material is difficult to recycle and has poor adsorption capacity when adsorbing PS microplastics.

[0007] The technical problem solved by the present invention can be achieved by adopting the following solutions: In one aspect, the present invention provides a method for preparing a metal organic framework magnetic material, comprising the following steps: Preparation of ferroferric oxide particles: dissolve ferrous chloride and ferric chloride in deionized water, and ultrasonically disperse for 10 to 15 minutes; heat the solution to 70°C to 80°C, drop 1 mol / L NaOH solution, adjust the pH to 12, and react for 30 to 40 minutes; after the reaction, wash and dry the product to obtain ferroferric oxide particles; Preparation of metal-modified metal-organic framework magnetic material Zn / MIL-101(Fe)@Fe3O4: dissolve the ferroferric oxide particles, ferric chloride and zinc chloride prepared in the above steps in N,N-dimethylformamide solution in turn, and ultrasonically disperse for 30-40 minutes; add terephthalic acid to the above solution and stir for 30-40 minutes; after stirring, transfer the solution to a hydrothermal reactor for hydrothermal reaction for 20-30 hours; recover the obtained product with a magnet, wash and dry the recovered product to obtain the metal-modified metal-organic framework magnetic material Zn / MIL-101(Fe)@Fe3O4.

[0008] Furthermore: in the step of preparing ferrosoferric oxide particles, the molar ratio of ferrous chloride to ferric chloride is 1:2.

[0009] Furthermore: in the step of preparing the metal-modified metal-organic framework magnetic material Zn / MIL-101(Fe)@Fe3O4, the molar ratio of ferrosoferric oxide to ferric chloride is 1:10.

[0010] Furthermore: in the step of preparing the metal-modified metal-organic framework magnetic material Zn / MIL-101(Fe)@Fe3O4, the molar ratio of zinc chloride to ferric chloride is (0.5-2):1.

[0011] Furthermore: in the step of preparing the metal-modified metal-organic framework magnetic material Zn / MIL-101(Fe)@Fe3O4, the molar ratio of terephthalic acid and ferric chloride is 1:2.

[0012] Furthermore: In the step of preparing the metal-modified metal-organic framework magnetic material Zn / MIL-101(Fe)@Fe3O4, the temperature of the hydrothermal reaction is 110°C.

[0013] Another aspect of the present invention provides a metal organic framework magnetic material prepared according to any one of the above preparation methods.

[0014] Another aspect of the present invention provides an application of the above-mentioned metal organic framework magnetic material for adsorbing and removing PS microplastics in water.

[0015] Further: when the metal-organic framework magnetic material is used to adsorb and remove PS microplastics in water, the metal-organic framework magnetic material is added to the wastewater to be treated, and the addition amount of the metal-organic framework magnetic material is 0.2-1.2 g / L.

[0016] In another aspect, the present invention provides a device for removing PS microplastics in water by loading the metal organic framework magnetic material, comprising a frame, a vortex oscillator base is arranged on the frame, an adsorption column is fixed on the vortex oscillator base through a sleeve, the metal organic framework magnetic material and wastewater containing PS microplastics are added into the adsorption column, and a sealing cover is detachably installed on the adsorption column; A moving frame is slidably installed on the frame, a ball screw is fixed on the moving frame, and the sealing cover includes a lifting part which is arranged on the moving frame and sleeved on the ball screw, a rotating part which is threadedly connected to the ball screw is rotatably installed below the lifting part, an electromagnet and a conductive ring electrically connected to the electromagnet are fixed on the rotating part, and a conductive sheet which contacts the conductive ring and is connected to a power supply is fixed on the lifting part; when the lifting part descends, it drives the rotating part to descend and rotate around the ball screw and then tightens it at the opening of the adsorption column, at which time the electromagnet extends into the adsorption column and is energized; when the lifting part rises, it drives the rotating part to rise and rotate around the ball screw and then rotates out from the opening of the adsorption column, and after rotating out, the movement of the moving frame drives the sealing cover and the electromagnet to move to the top of the recovery tank, and then the electromagnet loses power.

[0017] The beneficial effects of the present invention are as follows: (1) The preparation method of the metal organic framework magnetic material provided by the present invention, through a simpler and faster one-step solvent thermal method, MIL-101 (Fe) and Fe3O4 particles are compounded, and the Fe3O4 component is loaded to enable the metal organic framework material to have the ability to be separated by an external magnetic field, making it easy to recycle and reuse. Further secondary modification using Zn, the formed bimetallic coordination center greatly improves the electrostatic adsorption ability of the synthetic material to PS microplastics, and the addition of Zn improves the original pore structure of the material, which can provide more adsorption sites and increase the adsorption capacity for PS microplastics. The one-step solvent thermal preparation method simplifies the preparation process and reduces the preparation cost. (2) The metal organic framework magnetic material provided by the present invention, through the loaded Fe3O4, enables the MIL-101 (Fe) adsorption material with a bimetallic coordination center to have the ability to be recycled by an external magnetic field. Experiments have proved that the adsorption material of the present invention has high recycling and magnetization recovery rates, and has a strong adsorption capacity for PS microplastics. (3) The functional composite material synthesized by the present invention is applied to the process of adsorbing and removing PS microplastics in water. It has fast adsorption efficiency, excellent adsorption capacity and removal effect, and is simple to operate, has a wide pH application range, and has strong anti-ion interference ability, and has high practical application value. (4) The device provided by the present invention is conducive to the sufficient physical adsorption reaction between the metal organic framework magnetic material and the PS microplastics in the wastewater. After the reaction is completed, the metal organic framework magnetic material adsorbed with PS microplastics is separated and recovered by an electromagnet in a short time. The device has a high degree of automation and can automatically complete the sealing of the adsorption column by the sealing cover and the opening of the sealing cover. After the sealing cover is opened, the sealing cover and the electromagnet can be automatically moved to the recovery tank. After the electromagnet loses power, the metal organic framework magnetic material adsorbed with PS microplastics can be put into the recovery tank for recovery. The device for removing PS microplastics in water of the present invention can realize the continuous and efficient removal of PS microplastics in water by the metal organic framework magnetic material by the synthesized metal organic framework magnetic material, as well as the efficient recovery of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0019] Figure 1 This is a flow chart of a method for preparing a metal organic framework magnetic material of the present invention; Figure 2This is a schematic diagram of the structure of a device for removing PS microplastics in water loaded with metal organic framework magnetic materials according to the present invention; Figure 3 This is a schematic structural diagram from another angle of a device for removing PS microplastics in water loaded with metal organic framework magnetic materials according to the present invention; Figure 4 This is a structural schematic diagram from another angle of a device for removing PS microplastics in water loaded with metal-organic framework magnetic materials according to the present invention, with the adsorption column removed.

[0020] Figure 5 This is a structural schematic diagram from another angle of a device for removing PS microplastics in water loaded with metal-organic framework magnetic materials according to the present invention, with the adsorption column removed.

[0021] Figure 6 for Figure 4 A local enlarged view of point A; Figure 7 A cross-sectional view of a sealing cover of a device for removing PS microplastics in water loaded with a metal organic framework magnetic material according to the present invention; Figure 8 for Figure 7 A partial enlarged view of point B; Fig. 9 for Figure 7 A partial enlarged view of point C; Fig.10 for Figure 5 A partial enlarged view of point D; Fig.11 for Figure 3 A local enlarged view of point E; Fig.12 The effect of adsorption material dosage on removal rate and adsorption capacity; Fig.13 is the effect of the ratio of Zn to Fe substances on the removal rate of PS microplastics; Fig.14 The effect of reaction time on the removal rate of PS microplastics by Zn / MIL-101(Fe)@Fe3O4-1 and MIL-101(Fe)@Fe3O4; Fig.15 The effect of coexisting anions on the removal of PS microplastics by Zn / MIL-101(Fe)@Fe3O4-1 prepared in Example 2; Fig.16 The effect of pH on the removal of PS microplastics by Zn / MIL-101(Fe)@Fe3O4-1 prepared in Example 2; Fig.17 The effect of Zn / MIL-101(Fe)@Fe3O4-1 prepared in Example 2 on the cyclic adsorption of PS microplastics; Fig.18 The SEM scanning electron microscope images show that: (a) is the MIL-101(Fe)@Fe3O4 prepared in Comparative Example 1; (b) is the Zn / MIL-101(Fe)@Fe3O4-1 prepared in Example 2; (c) is the Zn / MIL-101(Fe)@Fe3O4-1 after the PS microplastics are adsorbed; Fig.19 It is the VSM diagram of Zn / MIL-101(Fe)@Fe3O4-1 in Example 2 and MIL-101(Fe)@Fe3O4 in Comparative Example 1; Fig. 20 XRD patterns of Zn / MIL-101(Fe)@Fe3O4-1 in Example 2 and MIL-101(Fe)@Fe3O4 in Comparative Example 1; Fig.21 FTIR infrared spectra of Zn / MIL-101(Fe)@Fe3O4-1 before and after adsorption of PS microplastics in Example 2 and MIL-101(Fe)@Fe3O4 in Comparative Example 1.

[0022] Main parts and numbers: Rack: 1; Mobile rack: 11; Slider: 111; Connecting arm: 112; Slide rail: 12; Vortex oscillator base: 21; sleeve: 22; adsorption column: 23; sealing cover: 24; lifting part: 241; T-shaped connecting piece 2411; rotating part: 242; T-shaped connecting groove: 2421; ball bearing: 243; sealing gasket: 244; water inlet pipe: 251; drain pipe: 252; Electromagnet: 31; conductive ring: 32; conductive sheet: 33; power supply: 34; Ball screw: 41; telescopic rod: 42; lifting motor: 43; Moving frame lead screw: 51; moving motor: 52; Recovery tank: 61; Collection tank: 62. DETAILED DESCRIPTION

[0023] In order to more clearly demonstrate the objectives, technical solutions and advantages of the present invention, the embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.

[0024] This embodiment provides a method for preparing a metal organic framework magnetic material, such as Figure 1 As shown, the preparation method comprises the following steps: S100, preparation of ferroferric oxide particles: S101, dissolve ferrous chloride and ferric chloride in deionized water, and disperse by ultrasonic for 10 min; S102, heating the above solution to 70°C, adding 1 mol / L NaOH solution dropwise, adjusting the pH to 12, and reacting for 30 minutes; S103, after the reaction is completed, the product is washed with deionized water until it is neutral, and dried at 60° C. to obtain ferrosoferric oxide particles; S200, preparation of metal-modified metal organic framework magnetic material Zn / MIL-101(Fe)@Fe3O4: S201, dissolving the ferroferric oxide particles, ferric chloride and zinc chloride prepared in the above steps in N,N-dimethylformamide solution in sequence, and performing ultrasonic dispersion for 30 min; S202, adding terephthalic acid to the above solution and stirring for 30 min; S203. After stirring, the solution was transferred to a hydrothermal reactor for hydrothermal reaction for 20 h. The obtained product was recovered by a magnet, washed several times with deionized water and anhydrous ethanol, and dried in vacuo at 60 °C to obtain a metal-modified metal organic framework magnetic material Zn / MIL-101(Fe)@Fe3O4.

[0025] After stirring, the solution was transferred to a hydrothermal reactor for hydrothermal reaction for 20 h. The obtained product was recovered by a magnet, washed several times with deionized water and anhydrous ethanol, and dried in a vacuum at 60 °C to obtain the metal-modified metal organic framework magnetic material Zn / MIL-101(Fe)@Fe3O4. Preferably, in the step of preparing ferrosoferric oxide particles, the molar ratio of ferrous chloride to ferric chloride is 1:2.

[0026] Preferably, in the step of preparing the metal-modified metal-organic framework magnetic material Zn / MIL-101(Fe)@Fe3O4, the molar ratio of ferrosoferric oxide to ferric chloride is 1:10.

[0027] Preferably, in the step of preparing the metal-modified metal organic framework magnetic material Zn / MIL-101(Fe)@Fe3O4, the molar ratio of zinc chloride to ferric chloride is (0.5-2): 1. Furthermore, the molar ratio of zinc chloride to ferric chloride is 1:1.

[0028] Preferably, in the step of preparing the metal-modified metal-organic framework magnetic material Zn / MIL-101(Fe)@Fe3O4, the molar ratio of terephthalic acid to ferric chloride is 1:2.

[0029] Preferably, the temperature of the hydrothermal reaction in step S203 is 110°C.

[0030] Another aspect of the present embodiment provides a metal organic framework magnetic material Zn / MIL-101(Fe)@Fe3O4, which is prepared by the above preparation method.

[0031] The metal organic framework magnetic material Zn / MIL-101(Fe)@Fe3O4 of this embodiment is used to adsorb and remove PS in water. In this embodiment, the PS is PS microplastics.

[0032] When the metal-organic framework magnetic material Zn / MIL-101(Fe)@Fe3O4 of this embodiment is used to adsorb and remove PS microplastics in water, the metal-organic framework magnetic material is mixed with the wastewater to be treated.

[0033] Preferably, the particle size of the PS microplastic is 1 μm. Preferably, the concentration of the pollutant PS microplastic in the wastewater is 300 mg / L.

[0034] Preferably, the dosage of the metal organic framework magnetic material in the wastewater to be treated is 0.2-1.2 g / L, and further, the dosage is 0.8 g / L.

[0035] Preferably, the pH value of the wastewater to be treated is 3 to 11. Further, the pH value of the wastewater to be treated is 3 to 10.

[0036] Preferably, the coexisting anions in the wastewater to be treated include Cl - 、HCO3 - 、CO3 2- and SO4 2- As a preference, the coexisting anion Cl - 、HCO3 - 、CO3 2- and SO4 2- The concentration of the coexisting anion Cl - 、HCO3 - 、CO3 2- and SO4 2- The concentration of the coexisting anion Cl - 、HCO3 - 、CO3 2- and SO4 2- The concentration was 100 mmol / L.

[0037] In order to ensure that the pollutant PS microplastics can be evenly dispersed in water, it is preferred that the PS microplastic solution is ultrasonically treated for 30 minutes before adsorption and removal.

[0038] like Figure 2 , 3As shown, another aspect of this embodiment provides a device for removing PS microplastics in water by loading the above-mentioned metal organic framework magnetic material, including a frame 1, a vortex oscillator base 21 is arranged on the frame 1, and an adsorption column 23 is fixed on the vortex oscillator base 21 through a sleeve 22, and the adsorption column 23 is used to add the above-mentioned metal organic framework magnetic material Zn / MIL-101(Fe)@Fe3O4 and wastewater containing PS microplastics. A sealing cover 24 is detachably installed on the adsorption column 23; the vortex oscillator base is a conventional component that allows the adsorption material in the container installed thereon to undergo a physical adsorption reaction with the pollutant, and it uses the vortex oscillation effect generated by the vortex oscillator base on the substance in the container, so that the adsorption material can be evenly dispersed in the reaction system, so that there is a sufficient mixing and adsorption effect between the adsorption material and the adsorbed pollutant. In this embodiment, under the vortex oscillation of the vortex oscillator base 21, a physical adsorption reaction occurs between the metal organic framework magnetic material Zn / MIL-101(Fe)@Fe3O4 in the adsorption column 23 and the PS microplastics in the wastewater, and the sealing cover 24 ensures the sealing of the adsorption column 23 during the adsorption process.

[0039] like Figure 4-6 As shown, a movable frame 11 is slidably installed on the frame 1, a ball screw 41 is fixed on the movable frame 11, and the sealing cover 24 includes a lifting part 241 arranged on the movable frame 11 for lifting and lowering, and a rotating part 242 rotatably installed below the lifting part 241, the lifting part 241 is sleeved on the ball screw 41, and the rotating part 242 is threadedly connected to the ball screw 41, and an electromagnet 31 capable of extending into the adsorption column 23 is fixedly installed below the rotating part 242, the electromagnet 31 is electrically connected to a conductive ring 32 fixed on the rotating part 242 through a conductive wire, a conductive sheet 33 connected to a power supply 34 through a conductive wire is fixed on the lifting part 241, and the power supply 34 is fixedly arranged on the movable frame 11, and the conductive sheet 33 is always in contact and connected with the conductive ring 32 during the process of the rotating part 242 rotating and driving the conductive ring 32 to rotate, so the electromagnet 31 can be connected to the power supply 34 through the conductive ring 32 and the conductive sheet 33.

[0040] When the lifting part 241 descends along the ball screw 41, the rotating part 242 is driven to descend along the ball screw 41. Since the rotating part 242 is threadedly connected to the ball screw 41, and the ball screw 41 is fixedly mounted on the moving frame 11, the rotating part 242 can rotate around the ball screw 41 while descending, and the rotating part 242 can be screwed on the open part of the adsorption column 23 during the process of descending and rotating. In this embodiment, an external thread (not shown in the drawings) is provided on the rotating part 242, and an internal thread (not shown in the drawings) is provided at the open part of the adsorption column 23, so that the rotating part 242 can be screwed and fixed on the open part of the adsorption column 23 during the process of descending and rotating, thereby sealing the adsorption column 23. When the adsorption column 23 is tightened at the open end of the adsorption column 23 , the electromagnet 31 extends into the adsorption column 23 , and the electromagnet 31 extending into the adsorption column 23 is energized through the conductive ring 32 and the conductive sheet 33 . The energized electromagnet 31 can attract the metal organic framework magnetic material adsorbed with PS microplastics in the adsorption column 23 .

[0041] When the lifting part 241 rises along the ball screw 41, it drives the rotating part 242 to rise along the ball screw 41. Since the rotating part 242 is threadedly connected to the ball screw 41, and the ball screw 41 is fixedly mounted on the moving frame 11, the rotating part 242 can rotate in the opposite direction around the ball screw 41 while rising. During the process of the rotating part 242 rising and rotating, it can be screwed out from the open part of the adsorption column 23. After being screwed out, the movement of the moving frame 11 can drive the sealing cover 24 and the electromagnet 31 on the rotating part 242 to move to above the recovery tank 61. The recovery tank 61 is fixedly mounted on the frame 1. The recovery tank 61 is used to hold ethanol or other washing liquid. Then, the power supply 34 is turned off to make the electromagnet 31 lose power. After the electromagnet 31 loses power, the metal organic framework magnetic material adsorbed with PS microplastics attracted thereon can be put into the washing liquid in the recovery tank 61 for washing and recovery, and the metal organic framework magnetic material removes the PS microplastics adsorbed on its surface in the washing liquid.

[0042] The specific connection relationship between the vortex oscillator base 21 and the adsorption column 23 is as follows: Figure 2 As shown, the sleeve 22 is fixedly disposed on the vortex oscillator base 21, and the adsorption column 23 is detachably fixedly connected to the sleeve 22 by bolts.

[0043] like Figure 7-9 As shown, in order to realize the rotational connection between the lifting part 241 and the rotating part 242 of the sealing cover 24, and in order to enable the lifting part 241 to drive the rotating part 242 to rise and fall when lifting, a T-shaped connecting piece 2411 is fixedly provided below the lifting part 241, and a T-shaped connecting groove 2421 is opened above the rotating part 242, and the T-shaped connecting piece 2411 is slidably installed in the T-shaped connecting groove 2421.

[0044] When the rotating portion 242 of the sealing cover 24 rotates relative to the lifting portion 241 , a ball 243 is provided between the rotating portion 242 and the lifting portion 241 to reduce friction between the rotating portion 242 and the lifting portion 241 and facilitate rotation of the rotating portion 242 .

[0045] In order to enhance the sealing performance between the sealing cover 24 and the adsorption column 23 and further ensure the sealing performance during the adsorption process in the adsorption column 23, as shown in FIG. Figure 5 , 10 As shown, a sealing gasket 244 is provided below the rotating portion 242 of the sealing cover 24 . After the rotating portion 242 of the sealing cover 24 is screwed onto the open portion of the adsorption column 23 , the sealing gasket 244 contacts the adsorption column 23 , thereby improving the sealing performance of the sealing cover 24 .

[0046] In order to facilitate the entry and discharge of wastewater, Figure 2 As shown, the adsorption column 23 is provided with an inlet pipe 251 for wastewater containing PS microplastics to enter, and the adsorption column 23 or the sleeve 22 is provided with a drain pipe 252 for the wastewater after adsorption treatment to be discharged. In this embodiment, the drain pipe 252 is arranged on the sleeve 22, and the drain pipe 252 arranged on the sleeve 22 is connected to the inside of the adsorption column 23. Valves (not shown in the drawings) for controlling the opening and closing of the water inlet pipe 251 and the drain pipe 252 are arranged on the water inlet pipe 251 and the drain pipe 252. A collection tank 62 is fixedly arranged on the frame 1, and the wastewater discharged from the drain pipe 252 can be discharged into the collection tank 62 for subsequent test experiments. In the process of wastewater entering the adsorption column 23 from the water inlet pipe 251 and the metal organic framework magnetic material in the adsorption column 23 and the wastewater containing PS microplastics undergoing physical adsorption reaction, the valve on the drain pipe 252 is closed to disconnect the connection between the drain pipe 252 and the collection tank 62. After the adsorption reaction is completed, the valve on the drain pipe 252 is opened so that the treated wastewater in the adsorption column 23 can be discharged into the collection tank 62 through the drain pipe 252 .

[0047] like Figure 2 , 5 As shown, in order to prevent the ball screw 41 fixedly installed on the moving frame 11 from accidentally tilting, a connecting arm 112 fixedly connected to the ball screw 41 is fixedly installed on the moving frame 11, and the connecting arm 112 is perpendicular to the ball screw 41.

[0048] In order to realize the lifting and lowering of the lifting part 241 on the moving frame 11, as shown in FIG. Figure 2 , 4As shown in Figures 5 and 6, a telescopic rod 42 is installed on the mobile frame 11, and the telescopic end of the telescopic rod 42 is fixedly connected to the lifting part 241 of the sealing cover 24, and the lifting and lowering of the lifting part 241 is achieved by the extension and retraction of the telescopic rod 42. In this embodiment, the telescopic rod 42 is an electric telescopic rod, and the telescopic rod 42 is driven by a lifting motor 43 fixedly installed on the mobile frame 11 to extend and retract.

[0049] like Figure 2 , 3 , 11, in order to realize the sliding of the mobile frame 11 along the frame 1, a mobile frame lead screw 51 is rotatably installed on the frame 1, the mobile frame 11 is threadedly connected to the mobile frame lead screw 51, a slide rail 12 is fixedly arranged on the frame 1, and a slider 111 (shown in Figure 3 , 11 When the moving frame lead screw 51 rotates, the moving frame 11 is driven to move along the moving frame lead screw 51, and when the moving frame 11 moves, the slider 111 thereon can slide along the slide rail 12. In this embodiment, the moving frame lead screw 51 is driven to rotate by a moving motor 52 fixedly arranged on the frame 1.

[0050] On the other hand, the present embodiment provides a method for removing PS microplastics from water by adsorption using the above-mentioned device, the method comprising the following steps: putting the metal organic framework magnetic material Zn / MIL-101(Fe)@Fe3O4 (adsorbent material) into the adsorption column 23, starting the lifting motor 43, extending the telescopic rod 42 to drive the lifting part 241 of the sealing cover 24 to descend, and then driving the rotating part 242 of the sealing cover 24 to rotate and descend, and the rotating part 242 is tightened and fixed to the open part of the adsorption column 23 during the rotation and descent process to seal the adsorption column 23, and then starting the power supply of the vortex oscillator base 21. The wastewater containing PS microplastics to be treated is discharged into the adsorption column 23 of the device through the water inlet pipe 251, so that the metal organic framework magnetic material Zn / MIL-101(Fe)@Fe3O4 in the adsorption column 23 and the PS microplastics in the wastewater undergo a physical adsorption reaction for a certain period of time. After the first reaction is completed, the power supply 34 is turned on to energize the electromagnet 31, thereby attracting the metal organic framework magnetic material adsorbed with PS microplastics to perform magnetic separation and recovery on the adsorbed material. Then, the lifting motor 43 is started again to shorten the telescopic rod 42 to drive the lifting part 241 of the sealing cover 24 to rise, and then drive the rotating part 242 of the sealing cover 24 to rotate and rise. The rotating part 242 is rotated out from the open part of the adsorption column 23 during the rotation and rising process, and the sealing cover 24 is opened. The moving motor 52 is started to drive the moving frame lead screw 51 to rotate, and the moving frame lead screw 51 drives the moving frame 11 to move when the moving frame lead screw 51 rotates. The movement of the moving frame 11 drives the sealing cover 24 and the electromagnet 31 on the rotating part 242 to move to the top of the recovery tank 61, and then the power supply 34 is turned off to make the electromagnet 31 lose power. After the power is lost, the metal organic framework magnetic material adsorbed with PS microplastics attracted on the electromagnet 31 can be put into the ethanol washing liquid in the recovery tank 61 for washing and recovery, and the metal organic framework magnetic material removes the PS microplastics adsorbed on its surface in the washing liquid. Afterwards, the treated wastewater in the adsorption column 23 is discharged into the collection tank 62 through the drain pipe 252 for subsequent testing experiments. Finally, new metal organic framework magnetic material is added to the adsorption column 23 to prepare for the next adsorption reaction.

[0051] Example 1: Preparation of ferroferric oxide particles: FeCl2•4H2O (0.8 g) and FeCl3•6H2O (2.3 g) (nFe(II):nFe(III) = 1:2) were dissolved in 40 mL of deionized water, and ultrasonic dispersion and stirring were performed for 10 min. 1 mol / L NaOH solution was added dropwise to the obtained solution at 70°C, and the pH was adjusted to 12, and the reaction was carried out for 30 min. After the reaction, the product was washed with deionized water until neutral, and dried at 60°C to obtain ferroferric oxide particles, and the precipitated product was recovered with a magnet.

[0052] Preparation of metal-modified metal-organic framework magnetic material Zn / MIL-101(Fe)@Fe3O4 (i.e., adsorption material): 0.058 g of Fe3O4 particles prepared by the above method, 0.675 g (2.45 mmol) FeCl3•6H2O and 0.334 g ZnCl2 (nZn(II):nFe(III) = 0.5:1) were dissolved in 30 mL N,N-dimethylformamide (DMF) and ultrasonically dispersed for 30 min; 0.206 g (1.24 mmol) terephthalic acid (H2BDC) was added and reacted with magnetic stirring for 30 min; the reaction product was heat treated at 110°C in a Teflon-lined autoclave for 20 h, recovered with a magnet, and washed several times with anhydrous ethanol and deionized water; finally, the obtained solid was vacuum dried at 60°C to obtain the metal-modified metal-organic magnetic material Zn / MIL-101(Fe)@Fe3O4-0.5.

[0053] Example 2: This example is different from Example 1 in that, when preparing the metal-modified metal-organic magnetic material Zn / MIL-101(Fe)@Fe3O4, the amount of ZnCl2 added is 0.668g, n Zn(II):n Fe(III) = 1:1, and the expression of the metal-modified metal-organic magnetic material finally obtained is Zn / MIL-101(Fe)@Fe3O4-1, and the rest is the same as Example 1.

[0054] Example 3: This example is different from Example 1 in that, when preparing the metal-modified metal-organic magnetic material Zn / MIL-101(Fe)@Fe3O4, the amount of ZnCl2 added is 1.336 g, n Zn(II):n Fe(III) = 2:1, and the expression of the final metal-modified metal-organic magnetic material is Zn / MIL-101(Fe)@Fe3O4-2, and the rest is the same as Example 1.

[0055] The following table shows the addition of zinc chloride in Examples 1 to 3:

[0056] Comparative Example 1: Preparation of ferroferric oxide particles: FeCl2•4H2O (0.8 g) and FeCl3•6H2O (2.3 g) (nFe(II):nFe(III) = 1:2) were dissolved in 40 mL of deionized water, and ultrasonic dispersion and stirring were performed for 10 min. 1 mol / L NaOH solution was added dropwise to the obtained solution at 70°C, and the pH was adjusted to 12, and the reaction was continued for 30 min. After the reaction, the product was washed with deionized water until neutral, dried at 60°C, and ferroferric oxide particles were obtained. The precipitated product was recovered with a magnet.

[0057] Preparation of metal-organic framework magnetic material MIL-101(Fe)@Fe3O4: 0.058 g of Fe3O4 nanoparticles prepared by the above method and 0.675 g (2.45 mmol) FeCl3•6H2O were dissolved in 30 mL N,N-dimethylformamide (DMF) and ultrasonically dispersed for 30 min; 0.206 g (1.24 mmol) terephthalic acid (H2BDC) was added and the reaction was stirred magnetically for 30 min; the reaction product was heat treated at 110°C in a Teflon-lined autoclave for 20 h, recovered with a magnet, and washed several times with anhydrous ethanol and deionized water; finally, the obtained solid was vacuum dried at 60°C to obtain the metal-organic framework magnetic material MIL-101(Fe)@Fe3O4.

[0058] Experimental example: Adsorption material performance test Wastewater containing PS microplastics is treated using the device provided in the specific embodiment and the method of using the device to adsorb and remove PS microplastics in water. The initial concentration of the PS solution is 300 mg / L, that is, the concentration of the PS solution entering the adsorption column 23 of the device through the water inlet pipe 251 is 300 mg / L, the volume of the PS solution added to the adsorption column 23 is 30 ml, and the duration of one adsorption reaction is 60 min. Take the treated wastewater in the collection tank 62, and use an ultraviolet spectrophotometer to measure the absorbance at a wavelength of 500 nm to calculate the residual concentration of PS. Removal rate η (%) and adsorption capacity q e (mg / g) is calculated by formula (1) and (2): (1) (2) Where, C0 (mg / L) is the initial concentration of PS solution; C t (mg / L) is the concentration of PS solution at time t (min), i.e., the residual concentration of PS; V (L) is the volume of PS solution added; W (g) is the mass of adsorbent material added.

[0059] Performance Test Example 1 MIL-101(Fe)@Fe3O4 prepared in Comparative Example 1 was selected as the adsorption material, and the effect of the dosage of the adsorption material on the removal rate was investigated. Fig.12The results show that within the dosage range of 0.2~1.2 g / L, the removal rate of PS microplastics gradually increased from 49% to 87.70%. When the dosage exceeded 0.8 g / L, the adsorption process of PS microplastics by MIL-101(Fe)@Fe3O4 tended to be flat. This is because the increase in the amount of adsorption materials provides more adsorption sites for PS microplastics, but when the amount of adsorption materials exceeds 0.8 g / L, the net increase in effective adsorption sites is very small, resulting in a slow increase in the removal rate. At the same time, the adsorption capacity of MIL-101(Fe)@Fe3O4 decreased from 735 mg / g to 234.54 mg / g. Therefore, considering the adsorption effect and cost control, the optimal dosage of adsorption materials selected in subsequent experiments is 0.8 g / L.

[0060] Performance Test Example 2 At the optimal adsorption dosage (0.8 g / L) selected by performance test example 1, the effects of the adsorption materials prepared in Examples 1 to 3 and Comparative Example 1 on the removal rate of PS microplastics were investigated. Fig.13 As shown in the figure, when the adsorption material dosage is 0.8 g / L, the removal rate of comparative example 1 is 86.22%, and the removal rates in Examples 1 to 3 increase with the increase of Zn addition. Among them, Zn / MIL-101(Fe)@Fe3O4-1 prepared in Example 2 has the highest removal rate of PS microplastics, reaching 94.46%. Therefore, based on the consideration of material preparation cost, Zn / MIL-101(Fe)@Fe3O4-1 was selected as the best adsorption material for subsequent experiments.

[0061] Performance Test Example 3 In order to explore the effect of time on the efficiency of adsorption materials in removing PS microplastics, under the condition of the optimal adsorbent dosage (0.8 g / L) selected in the above performance test example 1, the preferred adsorbent material Zn / MIL-101(Fe)@Fe3O4-1 (Example 2) in performance test example 2 and MIL-101(Fe)@Fe3O4 in comparative example 1 were selected for experiments. Fig.14 It can be found that the removal rates of Example 2 and Comparative Example 1 gradually tend to be flat with the increase of time and finally reach saturation. However, in the early stage of the adsorption process, the adsorption rate of Zn / MIL-101(Fe)@Fe3O4-1 is higher than that of MIL-101(Fe)@Fe3O4, which is because the addition of Zn enhances the electrostatic attraction between the adsorbent and PS microplastics during the adsorption process.

[0062] Performance Test Example 4 In order to explore the influence of coexisting anions on the efficiency of adsorbent materials in removing PS microplastics, under the condition of the optimal adsorbent material dosage (0.8 g / L) selected in the above performance test example 1, the preferred adsorbent material Zn / MIL-101(Fe)@Fe3O4-1 (Example 2) in performance test example 2 was selected for the experiment. - 、HCO3 - 、CO3 2- and SO4 2- ,like Fig.15 As shown in the figure, the order of the influence of coexisting anions on the removal rate of PS microplastics is CO3 2- > SO4 2- > HCO3 - >Cl - , and as the concentration increases, the adsorption efficiency (i.e., removal rate) of the adsorbent material on PS microplastics gradually decreases. 2- The removal of PS microplastics is most affected by CO3 2- Hydrolysis will occur, increasing the pH of the solution and reacting with Zn in Zn / MIL-101(Fe)@Fe3O4-1 2+ Combined with PS microplastics, insoluble ZnCO3 is generated, which weakens the complexation between the adsorbent material and PS microplastics.

[0063] Performance Test Example 5 In order to verify the effect of pH on the adsorption performance of the adsorption material, this test experiment investigated the adsorption of PS microplastics by Zn / MIL-101(Fe)@Fe3O4-1 prepared in Example 2 under different pH (3~11) environments. Fig.16 The effect of pH on the removal of PS microplastics by Zn / MIL-101(Fe)@Fe3O4-1, where the dosage of adsorbent material is 0.8 g / L. The results show that under acidic and weakly alkaline conditions, the removal rate of PS microplastics by Zn / MIL-101(Fe)@Fe3O4-1 can be maintained above 80%. When the pH is greater than 10, the removal rate and adsorption capacity are reduced, which is caused by repulsion in a strong alkaline environment.

[0064] Performance Test Example 6 In order to verify the recycling ability of the adsorption material, an adsorption cycle experiment was carried out with a dosage of 0.8 g / L of Zn / MIL-101(Fe)@Fe3O4-1. After one reaction, the adsorption material was separated from the mixed solution by an electromagnet, and the adsorption material was repeatedly washed with anhydrous ethanol. Finally, the adsorption material was vacuum dried at 60°C for the next adsorption experiment. A total of 5 cycles of adsorption reactions were performed. Fig.17 It can be seen that after five adsorption cycle experiments, the removal rate decreased compared with the first time, but it could still reach 83.81%, indicating that Zn / MIL-101(Fe)@Fe3O4-1 has good regeneration ability and has great potential for treating PS microplastics in water bodies.

[0065] Characterization test of adsorption materials 1 The morphology and microstructure of the preferred embodiment 2 and the comparative example 1 were characterized by scanning electron microscopy (SEM). Fig.18 As shown in (a), the MIL-101(Fe)@Fe3O4 crystals of Comparative Example 1 are uniform in size and stable in structure, showing a typical octahedral morphology. Fig.18 (b) is Zn / MIL-101(Fe)@Fe3O4-1 prepared in Example 2. It can be seen that the particle size of the adsorbent material is significantly reduced, indicating that the competitive coordination between the iron site and the doped metal (Zn) has an impact on the carboxyl group in H2BDC (terephthalic acid), improving its pore structure. Fig.18 (c) Zn / MIL-101(Fe)@Fe3O4-1 after adsorbing PS microplastics, which proves the successful adsorption of PS microplastics by the adsorption material.

[0066] Characterization test of adsorption materials 2 The magnetic properties of Example 2 and Comparative Example 1 were analyzed by a hysteresis loop tester (VSM). Fig.19 As shown, both Example 2 and Comparative Example 1 exhibit superparamagnetic properties with no remanence and no coercive force at room temperature, and their saturation magnetization values ​​are 13.60 emu / g and 9.37 emu / g, respectively, indicating that the saturation magnetization of the adsorption material modified with Zn is improved, and a magnet can be used for solid-liquid separation.

[0067] Characterization tests of adsorption materials 3 The Zn / MIL-101(Fe)@Fe3O4-1 of Example 2 and the MIL-101(Fe)@Fe3O4 of Comparative Example 1 were characterized by X-ray diffractometer (XRD). The results are as follows Fig. 20As shown, both adsorbent materials have characteristic peaks of MIL-101 (Fe) at 2θ=9.1° and 10.8°, indicating that both Example 2 and Comparative Example 1 retain the crystal structure of MIL-101 (Fe). Characteristic peaks belonging to Fe3O4 were observed at 2θ=30.08° (220), 35.43° (311), 43.05° (400), 56.94° (511), and 62.52° (440), confirming that the adsorbent material successfully loaded Fe3O4 magnetic particles, thereby having the ability of magnetic separation. Compared with Comparative Example 1, Example 2 has a new diffraction peak at 2θ=46.87°, which is because the added metal ions interact with the carboxyl groups in terephthalic acid (H2BDC) and react on the crystal structure. In addition, the diffraction peak intensity of Example 2 is weaker than that of Comparative Example 1, which is because the doped Zn competes with Fe for the metal center, resulting in a slight change in the crystal structure.

[0068] Characterization tests of adsorption materials 4 Fourier transform infrared spectroscopy (FTIR) was used to analyze the Zn / MIL-101(Fe)@Fe3O4-1 of Example 2 and the MIL-101(Fe)@Fe3O4 of Comparative Example 1. The characterization results are shown in Fig.21 middle, Fig.21 The Zn / MIL-101(Fe)@Fe3O4+PS in the figure represents Zn / MIL-101(Fe)@Fe3O4-1 after the PS microplastics are adsorbed. Fig.21 It can be observed that 518 cm -1 The peak at 746 cm corresponds to the stretching vibration of Fe-O in Fe3O4 nanoparticles. -1 The peak at 1400-1600 cm -1 The peaks in the range correspond to the symmetric and asymmetric stretching vibrations of the carboxyl group (-COO-) in the ligand terephthalic acid. The appearance of the above characteristic peaks proves the successful synthesis of the adsorbent material and its modification by Fe3O4 magnetic particles. In addition. -1 The characteristic peak of PS appeared at the surface, further confirming the effective adsorption of PS microplastics by Zn / MIL-101(Fe)@Fe3O4-1.

[0069] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a metal organic framework magnetic material, characterized in that: The steps include: Preparation of ferroferric oxide particles: dissolve ferrous chloride and ferric chloride in deionized water, and ultrasonically disperse for 10 to 15 minutes; heat the solution to 70°C to 80°C, add 1 mol / L NaOH solution, adjust the pH to 12, and react for 30 to 40 minutes; after the reaction, wash and dry the product to obtain Fe3O4 particles; Preparation of metal-modified metal-organic framework magnetic material Zn / MIL-101(Fe)@Fe3O4: The ferroferric oxide particles, ferric chloride and zinc chloride prepared in the above steps are dissolved in N,N-dimethylformamide solution in sequence, and ultrasonically dispersed for 30-40 min; terephthalic acid is added to the above solution and stirred for 30-40 min; after stirring, the solution is transferred to a hydrothermal reactor for hydrothermal reaction for 20-30 h; the obtained product is recovered by a magnet, and the recovered product is washed and dried to obtain the metal-modified metal-organic framework magnetic material Zn / MIL-101(Fe)@Fe3O4.

2. The method for preparing a metal organic framework magnetic material according to claim 1, characterized in that: In the step of preparing ferrosoferric oxide particles, the molar ratio of ferrous chloride to ferric chloride is 1:

2.

3. The method for preparing a metal organic framework magnetic material according to claim 1, characterized in that: In the step of preparing the metal-modified metal organic framework magnetic material Zn / MIL-101(Fe)@Fe3O4, the molar ratio of ferrosoferric oxide to ferric chloride is 1:

10.

4. The method for preparing a metal organic framework magnetic material according to claim 1, characterized in that: In the step of preparing the metal-modified metal organic framework magnetic material Zn / MIL-101(Fe)@Fe3O4, the molar ratio of zinc chloride to ferric chloride is (0.5-2):

1.

5. The method for preparing a metal organic framework magnetic material according to claim 1, characterized in that: In the step of preparing the metal-modified metal organic framework magnetic material Zn / MIL-101(Fe)@Fe3O4, the molar ratio of terephthalic acid and ferric chloride is 1:

2.

6. The method for preparing a metal organic framework magnetic material according to claim 1, characterized in that: In the step of preparing the metal-modified metal organic framework magnetic material Zn / MIL-101(Fe)@Fe3O4, the temperature of the hydrothermal reaction is 110°C.

7. A metal organic framework magnetic material, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 6.

8. An application of the metal organic framework magnetic material according to claim 7 for adsorbing and removing PS microplastics in water.

9. The use according to claim 8, characterized in that: When the metal organic framework magnetic material is used to adsorb and remove PS microplastics in water, the metal organic framework magnetic material is added to the wastewater to be treated, and the amount of the metal organic framework magnetic material added to the water is 0.2 to 1.2 g / L.

10. A device for removing PS microplastics in water by loading the metal organic framework magnetic material according to claim 7, comprising a frame (1), characterized in that: A vortex oscillator base (21) is arranged on the frame (1), an adsorption column (23) is fixed on the vortex oscillator base (21) through a sleeve (22), the adsorption column (23) is used to add the metal organic framework magnetic material and wastewater containing PS microplastics, and a sealing cover (24) is detachably installed on the adsorption column (23); A movable frame (11) is slidably mounted on the frame (1), a ball screw (41) is fixed on the movable frame (11), a sealing cover (24) comprises a lifting part (241) which is lifted and arranged on the movable frame (11) and sleeved on the ball screw (41), a rotating part (242) which is threadedly connected to the ball screw (41) is rotatably mounted below the lifting part (241), an electromagnet (31) and a conductive ring (32) which is electrically connected to the electromagnet (31) are fixed on the rotating part (242), and a power source (241) which contacts the conductive ring (32) and is connected to the power source (241) is fixed on the lifting part (241). When the lifting part (241) descends, it drives the rotating part (242) to descend and rotate around the ball screw (41) and then screws on the open part of the adsorption column (23). At this time, the electromagnet (31) extends into the adsorption column (23) and is energized. When the lifting part (241) rises, it drives the rotating part (242) to rise and rotate around the ball screw (41) and then screws out from the open part of the adsorption column (23). After screwing out, the movement of the moving frame (11) drives the sealing cover (24) and the electromagnet (31) to move to the top of the recovery tank (61), and then the electromagnet (31) loses power.